2017
DOI: 10.5812/ijp.9416
|View full text |Cite
|
Sign up to set email alerts
|

The Neutrophil Lymphocyte Ratio as a Successful Extubation Predictor of Prolonged Intubation in Pediatric Heart Surgery

Abstract: Background: Postoperative mechanical ventilation is required in patients undergoing congenital heart surgery. However, the duration of mechanical ventilation may be extended as a result in some patients. Inflammation is a normal and expected process following surgery and the intensive care process. However, increased and prolonged inflammation increases the risk of mortality and morbidity. The neutrophil lymphocyte ratio (NLR) can be used as a new marker of inflammation in cardiovascular diseases. The aim of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Many potential prognostic and predictive molecular inflammatory biomarkers have now been identified in the evaluation of poor outcomes following CPB; however, none have yet entered into clinical practice. Accumulating evidence demonstrated that NLR could reflect a systemic inflammatory response (17, 18); however, there is only one study evaluating the prognosis associations of NLR in pediatric patients with CPB (19). According to the results of the study, the NLR measured before extubation displayed significantly more variation in pediatric patients with failed extubation; less variation in NLR was found in children in whom extubation was successful (20).…”
Section: Discussionmentioning
confidence: 99%
“…Many potential prognostic and predictive molecular inflammatory biomarkers have now been identified in the evaluation of poor outcomes following CPB; however, none have yet entered into clinical practice. Accumulating evidence demonstrated that NLR could reflect a systemic inflammatory response (17, 18); however, there is only one study evaluating the prognosis associations of NLR in pediatric patients with CPB (19). According to the results of the study, the NLR measured before extubation displayed significantly more variation in pediatric patients with failed extubation; less variation in NLR was found in children in whom extubation was successful (20).…”
Section: Discussionmentioning
confidence: 99%
“…46,54,60 In a study by Savluk et al, NLR varied between children with failed and successful extubation (following prolonged intubation). 61 Moreover, a high preoperative NLR was associated with acute kidney injury after tetralogy of Fallot repair. 62 Therefore, NLR may be used to identify patients at risk of postoperative complications.…”
Section: Postoperative Complicationsmentioning
confidence: 99%